The Cardiomyopathy Registry of the EURObservational Research Programme of the European Society of Cardiology: baseline data and contemporary management of adult patients with cardiomyopathies. (24th January 2018) - Charron, Philippe; Elliott, Perry M; Gimeno, Juan R; Caforio, Alida L P; Kaski, Juan Pablo; Tavazzi, Luigi; Tendera, Michal; Maupain, Carole; Laroche, Cécile; Rubis, Pawel; Jurcut, Ruxandra; Calò, Leonardo; et al.
Abstract: Aims: The Cardiomyopathy Registry of the EURObservational Research Programme is a prospective, observational, and multinational registry of consecutive patients with four cardiomyopathy subtypes: hypertrophic cardiomyopathy (HCM), dilated cardiomyopathy (DCM), arrhythmogenic right ventricular cardiomyopathy (ARVC), and restrictive cardiomyopathy (RCM). We report the baseline characteristics and management of adults enrolled in the registry. Methods and results: A total of 3208 patients were enrolled by 69 centres in 18 countries [HCM ( n = 1739); DCM ( n = 1260); ARVC ( n = 143); and RCM ( n = 66)]. Differences between cardiomyopathy subtypes ( P < 0.001) were observed for age at diagnosis, history of familial disease, history of sustained ventricular arrhythmia, use of magnetic resonance imaging or genetic testing, and implantation of defibrillators. When compared with probands, relatives had a lower age at diagnosis ( P < 0.001), but a similar rate of symptoms and defibrillators. When compared with the Long-Term phase, patients of the Pilot phase (enrolled in more expert centres) had a more frequent rate of familial disease ( P < 0.001), were more frequently diagnosed with a rare underlying disease ( P < 0.001), and more frequently implanted with a defibrillator ( P = 0.023). Comparing four geographical areas, patients from Southern Europe had a familial disease more frequently ( P < 0.001), were more frequently diagnosed in the context of a family screening ( P < 0.001), and more frequently diagnosed with a rare underlying disease ( P < 0.001). Conclusion: By providing contemporary observational data on characteristics and management of patients with cardiomyopathies, the registry provides a platform for the evaluation of guideline implementation. Potential gaps with existing recommendations are discussed as well as some suggestions for improvement of health care provision in Europe.